Rot, Weiss & Blau - Leeson, Robert,Krutz-Arnold, Cornelia,Fosshag, Bengt (Klopp, 1997)
A transfer student in a new city, Wain writes about his life in three different versions: the real truth on red paper in the form of letters to an imaginary pen pal; the
Keywords: Jugendbuch; Imaginary playmates; Imagination; Student adjustment; Transfer students; Truth; Streit; Kreatives Schreiben; Vaterentbehrung; Bruder; Junge